Daily field checking list by Walter Rosene, April 28, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 28, 1932. This checklist was used by Walter Rosene to record birds sighted around Schall Pond and Beaver Bayou with Bob Walker between 6:30 and 9:00. Plustek--flatbed